Tumour necrosis factor inhibitor survival and predictors of response in axial spondyloarthritis—findings from a United Kingdom cohort - Yahya, Fariz; Gaffney, Karl; Hamilton, Louise; Lonsdale, Ellie; Leeder, Jane; Brooksby, Alan; Cavill, Charlotte; Berry-Jenkins, Joshua; Boyle, Cathal; Bond, Debbie; Sengupta, Raj (Oxford University Press, 2017)
Objectives. To analyse long-term survival and efficacy of TNFi, reasons for switching or discontinuing, baseline predictors of response and remission in axial spondyloarthritis (axSpA) patients in a UK cohort. Methods. All patients with a physician-verified diagnosis of axSpA attending two specialist centres who fulfilled the eligibility criteria for TNFi were included. Routinely recorded patient data were reviewed retrospectively. Initial TNFi was recorded as the index drug. Results. Six hundred and fifty-one patients (94% AS) were included; adalimumab (n = 332), etanercept (n = 205), infliximab (n = 51), golimumab (n = 40) and certolizumab pegol (n = 23) were index TNFi. The mean (S.D.) duration from symptom onset to time of diagnosis was 8.6 (8.7) years and mean (S.D.) duration from diagnosis to TNFi initiation was 12.6 (11.5) years. A total of 224 (34.4%) stopped index TNFi, and 105/224 switched to a second TNFi. Median drug survival for index and second TNFi were 10.2 years (95% CI: 8.8, 11.6 years) and 5.5 years (95% CI: 2.7, 8.3 years), respectively (P < 0.05). Survival rates were not influenced by choice of TNFi. HLA-B27 predicted BASDAI50 and/or two or more point reduction within 6 months and long-term drug survival (P < 0.05). Low disease activity was predicted by non-smoking and low baseline BASDAI (P < 0.05). Conclusion. We have observed good TNFi survival rates in axSpA patients treated in a real-life setting. This is best for first TNFi and not influenced by drug choice.